An Application of Differential Search Algorithm in Solving Non-Convex Economic Dispatch Problems with Valve-Point Effects - M. H., Sulaiman (Praise Worthy Prize, 2013)
This paper presents an application of Differential Search (DS) algorithm for solving non-convex economic dispatch (ED) problems with the valve loading effects. ED is one of the most challenging problems of power system since it is difficult to determine the optimum generation scheduling to meet the particular load demand with the minimum fuel costs while all constraints are satisfied. In addition, the practical ED problems which are involving non-convex objective functions with equality and inequality constraints including the practical operation constraints of generators such as ramp rate limit, prohibited operating zones and generation limits make it harder to solve the global optimum using conventional methods. In this paper, DS is adopted to find the global optimum results of ED. To demonstrate the effectiveness and feasibility of DS in solving ED, four well known ED test systems with non-convex solution features have been tested and compared with some of the most recently published ED solution methods in literature. The results of this research show that DS is able to find more economical solution than those determined by other methods.